(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
On the basis of experimental studies, the optimal technological parameters of the solar chamber have been established, such as the filling factor of the chamber with freshly laid concrete, the distance from the top of the concrete to the bottom of the solar coating from the position of the best heating and the increase in the strength of concrete in the solar chamber by ensuring the daily turnover of forms, as well as the physical processes taking place in it.